2014
DOI: 10.1177/0011392114534422
|View full text |Cite
|
Sign up to set email alerts
|

History of sociology and the quest for intellectual autonomy in the Global South: The cases of Alberto Guerreiro Ramos and Syed Hussein Alatas

Abstract: History of sociology is one of the main fields within the broader area of social science research. Despite its growing methodological sophistication, the field still lacks a truly global approach, one that takes into account alternative sociological traditions, particularly those from the so-called Global South. This article seeks to address these shortcomings by proposing a case study comparison between two sociologists from the Global South who developed similar sociological discourses between the 1950s and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 30 publications
0
9
0
5
Order By: Relevance
“…More reflections of this type in our area would improve self-reflexivity and thus help us critically examine many of the hidden assumptions that shape our national debates. Additionally, a greater knowledge of other peripheral intellectual traditions which have dealt with similar problems and issues can help scholars of Brazilian social thought to make meaningful contributions to international debates (Maia, 2014). Finally, I believe that one of the main dilemmas to be faced by researchers in the field of Brazilian social thought refers to the political status of their objects, which are deeply interwoven with the very construction of the nation-state.…”
Section: Final Considerationsmentioning
confidence: 96%
See 1 more Smart Citation
“…More reflections of this type in our area would improve self-reflexivity and thus help us critically examine many of the hidden assumptions that shape our national debates. Additionally, a greater knowledge of other peripheral intellectual traditions which have dealt with similar problems and issues can help scholars of Brazilian social thought to make meaningful contributions to international debates (Maia, 2014). Finally, I believe that one of the main dilemmas to be faced by researchers in the field of Brazilian social thought refers to the political status of their objects, which are deeply interwoven with the very construction of the nation-state.…”
Section: Final Considerationsmentioning
confidence: 96%
“…A third example is in my own work (Maia, 2014) about Guerreiro Ramos. In analyzing the theoretical construction of this Brazilian sociologist, I placed him alongside other peripheral social scientists of the 1950s and 1960s who also thought about the role of theory developed in central capitalist countries in peripheral contexts.…”
Section: Brazilian Social Thought: Some Recent Trendsmentioning
confidence: 99%
“…In fact, there are numerous scholars who have contributed meaningful knowledge throughout the centuries who have been neglected, ignored or forgotten, especially those from the non-West. One would think that someone who has been described as 'one of the founders of sociological investigation in Southeast Asia' (Abaza 2005: 237) would be well-known, but regrettably, Syed Hussein Alatas is still under appreciated in the dominant centres of knowledge production (Graf 2010;Maia 2014). Alatas was of Arab heritage but was born and raised in Indonesia, completed his doctorate in the Netherlands, and subsequently resided within Singapore and Malaysia.…”
Section: Syed Hussein Alatas (1928-2007)mentioning
confidence: 99%
“…For instance, he suggested that '[t]he teachings of Hindu, Buddhist, Islamic and Chinese sages are excellent sources of the anti-corruption outlook ' (2015 [1968]: 94). Indeed, Alatas' Muslim faith influenced his scholarship as he sought to reconcile religion with modernity in a manner that allowed him to promote religious themes throughout his work (Maia 2014(Maia : 1104(Maia -1107. In one instance, he even proposed religion as a solution to the criminological question: 'What keeps the population stable and restrained from committing crimes and evil acts?'…”
Section: Alatas On Crimes Of the Powerfulmentioning
confidence: 99%
“…Apesar da visão colonial e colonizadora que as próprias ciências sociais ajudam a difundir, os trânsitos sul-atlânticos já permitem aos olhares mais atentos reconhecer desafios teóricos metodológicos propostos nestas bandas do mundo (Nyamnhjoh, 2012; Adesina, 2002, Maia, 2014. Aqui, talvez, a metáfora da dupla consciência, forjada por W. E. B. Dubois, para falar da condição do negro nos Estados Unidos do final do Século XIX, seja a mais apropriada para lidar com os desafios de se fazer sociologia no Sul do mundo.…”
unclassified